THE EFFECT OF WORKLOAD ON EMPLOYEE PERFORMANCE WITH BURNOUT AS AN INTERVENING VARIABLE AT BANK BTN KCP CIKUPA - Setiawan, Tori; Yulistiyono, Agus (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the effect of workload on employee performance with burnout as an intervening variable at Bank BTN KCP Cikupa. A high workload is often a major factor influencing employee stress and burnout levels, which can ultimately lead to decreased performance. This research employs a quantitative approach using a survey method involving employees of Bank BTN KCP Cikupa as respondents. Data were collected through questionnaires and analyzed using path analysis to examine the relationships between the independent variable, intervening variable, and dependent variable. The results indicate that workload has a significant effect on employee burnout. Furthermore, burnout serves as a mediating variable that weakens the relationship between workload and employee performance. In other words, the higher the workload, the greater the burnout experienced by employees, which ultimately negatively impacts their performance. Therefore, companies are advised to manage workload effectively to reduce burnout risks and enhance employee performance.